Characterization of carbonaceous aerosols in Asian outflow in the spring of 2015: Importance of non-fossil fuel sources. (1st October 2019) - Miyakawa, T.; Komazaki, Y.; Zhu, C.; Taketani, F.; Pan, X.; Wang, Z.; Kanaya, Y.
Abstract: The sources of elemental (EC) and organic carbon (OC) aerosols in Asian outflow were investigated in the spring of 2015 in terms of radiocarbon ( 14 C) and molecular marker analyses. The contribution of fossil fuel (FF) sources to carbonaceous aerosols (TC) significantly increased in polluted air masses with enhancements in the concentrations of carbon monoxide. For EC, FF sources dominated in the polluted air masses. For OC, the contributions of non-FF sources other than biomass burning (BB) were found to be significant (comparable to or higher than those of FF sources), especially in air masses with higher values of the water-soluble fraction of OC (fWSOC ) and 14 C concentrations (F 14 C). Positive correlations between fWSOC and F 14 C indicate that the origins of TC (mainly OC) have great impacts on the water solubility variability and the subsequent cloud formation processes of OC during transport. We found the importance of natural sources as possible origins of OC in non-polluted (i.e., background) air. This study raises the need to further investigate the source apportionment of OC, especially its natural origins, for more accurately assessing the climatic impacts of EC and OC in East Asia. Graphical abstract: Image 2 Highlights: Source apportionment of carbonaceous aerosols in Asian outflow in the spring of 2015 was investigated in a Japanese remote island. Biomass burning was not dominant emission process of carbonaceous aerosols at the observation site through the observation period. Black carbon aerosols were mostly emitted from fossil fuel (FF) sources. (~90%). 4Organic carbon (OC) aerosols were significantly affected by non-FF sources as well as FF sources. Major portion of non-FF-derived OC was likely originated from natural sources such as ocean and land vegetation. Mixing between polluted and background air masses in Asian outflow regulated the water-soluble fraction of OC as well as source apportionment.